The Effect of Immersion Time on the Longevity of Puffy Fish (Rastrelliger Sp.) Fresh Using Beluntas (Pluchea Indica L.) Leaf Extract - Cono, Upriyanto; Husain, Rahim; Yusuf, Nikmawatisusanti (European Journal of Life Safety and Stability (2660-9630), 2021)
This study aims to determine the effect of beluntas leaf extract (Pluchea indica L.) on the quality of fresh mackerel (Rastrelliger sp.). Treatment factors were beluntas leaves with a concentration of 100% for 3 hours, 6 hours, 9 hours, 12 hours and 15 hours. This study was designed using RAL for chemical and microbiological test results, while organoleptic data were analyzed by Kruskall-wallis. All data that had a significant effect were tested by Duncan’s further test. The results showed that fresh mackerel (Rastrelliger sp.) soaked in 100% solution of beluntas (Pluchea indica L.) indicated that the immersion time had a significant effect on the hedonic quality of the eyes, gills, mucus, odor, flesh and texture of mackerel. . The organoleptic value of hedonic quality at immersion time of up to 15 hours meets the standard of SNI 2729-2013 concerning fresh fish for all hedonic quality parameters with a value of 7. The treatment duration of immersion up to 15 hours had a significant effect on the amount of TPC with values between 4.62 CFU/gr – 5.57 CFU/gr and pH ranging from 6.13 – 6.42. These results still meet the requirements of SNI 2729-2013 regarding fresh fish.